The age of immunology : conceiving a future in an alienating world - Napier, A. David (University of Chicago Press, 2003)
In this fascinating and inventive work, A. David Napier argues that the central assumption of immunology--that we survive through the recognition and elimination of non-self--has become a defining concept of the modern age. Tracing this immunological understanding of self and other through an incredibly diverse array of venues, from medical research to legal and military strategies and the electronic revolution, Napier shows how this defensive way of looking at the world not only destroys diversity but also eliminates the possibility of truly engaging difference, thereby impoverishing our cultur.